Measurement of electrode–tissue interface impedance for improvement of a transcutaneous data transmission using human body as transmission medium - Okamoto, Eiji; Kato, Yoshikuni; Kikuchi, Sakiko; Mitamura, Yoshinori (Bio-medical materials and engineering, 2014)
The electrical property between an electrode and skin or tissue is one of the important issues for communication performance of the transcutaneous communication system (TCS) using a human body as a conductive medium. In this study, we used a simple method to measure interface resistance between the electrode and skin on the surface of the body. The electrode–electrode impedance was measured by a commercially available LCR meter with changes in the distance between two electrodes on an arm of a healthy male subject, and we obtained the tissue resistivity and electrode–skin interface resistance using the cross-sectional area of the arm. We also measured transmission gain of the TCS on the surface of the body, and we investigated the relationship between electrode–skin interface resistance and transmission gain. We examined four kinds of electrodes: a stainless steel electrode, a titanium electrode, an Ag–AgCl electrode and an Ag–AgCl paste electrode. The stainless steel electrode, which had lower electrode–skin resistance, had higher transmission gain. The results indicate that an electrode that has lower electrode–skin resistance will contribute to improvement of the performance of the TCS and that electrode–skin interface resistance is one of valuable evaluation parameters for selecting an optimum electrode for the TCS.